Clonal analysis as a prognostic factor in multiple oral squamous cell carcinoma. (April 2017) - Gissi, D.B.; Tarsitano, A.; Leonardi, E.; Gabusi, A.; Neri, F.; Marchetti, C.; Montebugnoli, L.; Foschini, M.P.; Morandi, L.
Highlights: mtDNA analysis is a molecular method to evaluate the clonality of secondary tumors. mtDNA analysis differentiated 23 OSCCs in 7 LRs, 4 SPTs and 12 SFTs. SFTs showed a better survival rate with respect to LRs and SPTs. mtDNA analysis may influence the prognosis and treatment in multiple OSCCs. Abstract: Objectives: A novel classification based on molecular methods to assess clonality defines three types of secondary oral squamous cell carcinoma (OSCC): second primary tumour (SPT) independent from the index tumour, local recurrence (LR), clonally related to the primary tumour, and second field tumour (SFT), derived from the same genetically altered mucosal field as the primary tumour. The present study applied mtDNA analysis in a group of patients experiencing a second loco-regional neoplastic manifestation. The purpose was to differentiate secondary tumours into LRs, SPTs and SFTs and evaluate the prognostic impact in terms of survival rate. Material and methods: The study population comprised 23 patients who experienced a second neoplastic lesion after a surgical resection of primary OSCC. mtDNA D-loop analysis was applied in paired neoplastic lesions and in clinically and histologically normal mucosa. On the basis of mtDNA results, the second OSCC was classified as LR or SPT or SFT. Disease-free survival was defined as the duration between the appearance of the second neoplastic lesion and death of disease, or last follow-up visit. Results: Seven secondary tumours were classified as LR, 12 as SFT, 4 as SPT. An altered mucosal field proved a variable significantly related to a better survival rate (p < 0.05); 2/12 (16.6%) SFT events failed as compared to 5/7 LRs (71.4%) and 3/4 SPTs (75%). Conclusion: mtDNA analysis may be considered a useful tool to differentiate secondary tumours and might influence the choice of the most appropriate treatment in patients with multiple OSCCs.